Use of ambulatory blood pressure monitoring in the gestational hypertensive disorders - Prado, Pâmela Fernanda; Silva, Stael Silvana Bagno Eleutério da (ABCS Health Sciences, 2017)
Pregnancy is a physiological phenomenon, but gestational harm to maternal and fetal health may occur during its progress. Gestational hypertensive disorders are responsible for high rates of maternal and perinatal morbidity and mortality, and are considered the leading cause of direct obstetric deaths, representing a major public health issue. It is known that there are significant differences between the casual blood pressure measured at home and that obtained at the outpatient and/or hospital levels. Therefore, the use of ambulatory blood pressure monitoring (ABPM) is an important strategy used in the prevention of hypertension, because it allows the accurate evaluation of blood pressure through a systematized and efficient registry in the diagnosis and control of the disease. Scientific research confirms the importance of ABPM in relation to hypertensive disorders, mainly highlighting its correlation with the values obtained when compared to the casual measure and residential pressure measurement. Under these circumstances, this study concluded that ABPM is an advantageous tool in the control of blood pressure and care for pregnant women. The assistance provided by obstetrician nurses with the use of ABPM is relevant because it minimizes the possibility of fetal and maternal death by hypertension, enabling plans of care based on pressure levels more reliable than the casual measure.